Ventricular Septal Rupture Complicating Acute Myocardial Infarction: A Preventable Complication? Case Report and Review of the Literature - Nadhil, Zayna; Mehssani, Zineb; Lakhal, Zouhair (RA Journal of Applied Research, 2022)
Despite the significant reduction in mortality from acute myocardial infarction in recent decades due to adequate medical management, cardiac monitoring, and early reperfusion, the mortality rate from ventricular septal rupture remains considerable. The risk factors for this complication have been the subject of several studies such as hypertension, advanced age, female gender, absence of angina pectoris, and anterior location of the ischemia. Surgical repair techniques have evolved over time, but the prognosis remains very poor with a mortality rate unchanged since 1990. This is why it is very important to know the clinical manifestations to specify the diagnosis by echocardiography and to allow urgent medical and surgical management. We will illustrate this fatal complication of myocardial infarction and review the different factors that predict its development through a clinical case and a review of the literature.